Fungal microbiomes associated with green and non-green building materials. (November 2017) - Coombs, Kanistha; Vesper, Stephen; Green, Brett J.; Yermakov, Mikhail; Reponen, Tiina
Abstract: Water-damaged buildings can lead to fungal growth and occupant health problems. Green building materials, derived from renewable sources, are increasingly utilized in construction and renovations. However, the question as to what fungi will grow on these green compared to non-green materials, after they get wet, has not been adequately studied. By determining what fungi grow on each type of material, the potential health risks can be more adequately assessed. In this study, we inoculated green and non-green pieces of ceiling tile, composite board, drywall, and flooring with indoor dust containing a complex mixture of naturally occurring fungi. The materials were saturated with water and incubated for two months in a controlled environment. The resulting fungal microbiomes were evaluated using ITS amplicon sequencing. Overall, the richness and diversity of the mycobiomes on each pair of green and non-green pieces were not significantly different. However, different genera dominated on each type of material. For example, Aspergillus spp. had the highest relative abundance on green and non-green ceiling tiles and green composite boards, but Peniophora spp. dominated the non-green composite board. In contrast, Penicillium spp. dominated green and non-green flooring samples. Green gypsum board was dominated by Phialophora spp. and Stachybotrys spp., but non-green gypsum board by Myrothecium spp. These data suggest that water-damaged green and non-green building materials can result in mycobiomes that are dominated by fungal genera whose member species pose different potentials for health risks. Graphical abstract: Highlights: Mycobiomes on green and non-green products were similar in richness and diversity. Aspergillus spp. and Peniophora spp. dominated ceiling tiles and composite board, green or not. Penicillium spp. was the most common fungal genus on green and non-green flooring. Phialophora spp. and Stachybotrys spp. dominated green gypsum board; Myrothecium on non-green.